Pembentukan Karakter Islami Siswa Melalui Mentoring Tarbawi Di Sekolah Menengah Islam Pertama Terpadu Al-Fityan School Gowa - Nurul Ilmah; Rusli Malli; Mukhlis Madani (Universitas Muslim Indonesia, 2022)
This study aims to identify and analyze: 1. Implementation of the tarbawi mentoring program at SMPIT Al-Fityan School Gowa. 2. Factors that hinder the tarbawi mentoring program at SMPIT Al-Fityan School Gowa. 3. The results of the tarbawi mentoring program in shaping the Islamic character of students at SMPIT Al-Fityan School Gowa. The tarbawi mentoring program at SMPIT Al-Fityan School Gowa is one of the methods used by schools to shape and foster student character in a more specific scope (small group The general purpose of tarbawi mentoring activities is as an effort to assist and direct students in learning more about Islamic teachings and applying these Islamic values in their daily lives. So that students are expected to have good Islamic knowledge and noble character ( morals ). This research is descriptive qualitative, which is a research that is intended to reveal an empirical fact in a scientific objective based on scientific logic, procedures and supported by a strong methodology and theory according to the scientific discipline being occupied. The results of this study indicate that the implementation of the tarbawi mentoring program provides a positive role on student behavior both in relation to Allah SWT (hablun minallah) and their relationship with fellow human beings (hablun minannas).